Efektifitas Positive Deviance Hearth (Pos Gizi) untuk Perbaikan Anak Kurang Gizi di Perkotaan Surabaya, Indonesia: The Effectiveness of Positive Deviance Hearth (Pos Gizi) to Improve Malnourished Children in Urban Surabaya, Indonesia - Nur Mufida Wulan Sari; Martina Puspa Wangi; Hasanah Ayuningtyas; Allyra Himawati; Suci Handayani; Fitria Nurus Sakinah; Daniel Andi Kristanto; Anggiat Manahan; Andi Nugroho; Nur Sahila; Charles Frans; Trias Mahmudiono (Universitas Airlangga, 2023)
Background: Positive Deviance Heart (PDH) focuses on processes identifying affordable, acceptable, and sustainable practices used in communities with limited resources. One of PDH's goals is to prevent malnutrition in children by changing societal norms regarding parenting behavior, feeding practices, and health care behavior. Objectives: This study aimed to determine the effectiveness of PDH implementation in urban areas by assessing nutritional status alteration and changes in child feeding practices. Methods: This quantitative study with a descriptive-analytic approach used secondary data from a three-month PDH intervention conducted by Wahana Visi, Indonesia. Locations and participants were determined by a purposive sampling method. Twenty-nine (29) participants from three urban villages in Surabaya were involved. Data analysis was performed using frequency distribution, ANOVA, and Chi-square test (95% Confidence Interval). Results: The PDH implementation in Simokerto Sub-district did not significantly improve the children's nutritional status. Changes in child feeding practices during the Hearth did not significantly affect children's nutritional status (p>0.05). There were differences (p<0.05) in Z-score alteration based on the time of weighing with or without considering the age groups and the children's residence (p<0.05). Conclusions: The three-month PDH sessions in the Simokerto Sub-district have not been effective in increasing the target of nutritional status. Changes in child feeding practices were not associated with increased children's nutritional status. Based on the time of weighing, the PDH's intervention periods can improve the target of nutritional status.